2001
DOI: 10.1097/00000539-200101000-00038
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine Combined with a Long Acting Local Anesthetic Does Not Prolong Postoperative Analgesia after Brachial Plexus Block but Does Induce Hemodynamic Changes

Abstract: Clonidine in brachial plexus block does not improve postoperative analgesia when mixed with a long-lasting anesthetic. Nevertheless, with or without clonidine, bupivacaine in interscalene block provides a long-lasting analgesia of approximately 15 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 13 publications
5
84
0
2
Order By: Relevance
“…The two groups showed no clinically significant difference in onset and duration of motor and sensory blockade. 18 Sedation after provision of block was assessed using the sedation score described by Culebras et al 5 The results of our study were similar to those obtained by Agarwal S et al where dexmedetomidine was added to bupivacaine and sedation was assessed using modified Ramsay sedation score. 19 They observed that patients who received dexmedetomidine had higher sedation scores.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The two groups showed no clinically significant difference in onset and duration of motor and sensory blockade. 18 Sedation after provision of block was assessed using the sedation score described by Culebras et al 5 The results of our study were similar to those obtained by Agarwal S et al where dexmedetomidine was added to bupivacaine and sedation was assessed using modified Ramsay sedation score. 19 They observed that patients who received dexmedetomidine had higher sedation scores.…”
Section: Discussionsupporting
confidence: 83%
“…Grade 2: Complete motor block with inability to move below wrist and fingers. Sedation was assessed using sedation score described by Culebras et al 5 Score 1: Awake and alert. Score 2: Sedated, responding to verbal stimulus.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, mixed epinephrine to bupivacaine could have masked any pharmacodynamic effect of perineural magnesium, similar to the report in which clonidine failed to prolong the analgesic duration of ropivacaine and bupivacaine with epinephrine. 15 In conclusion, the addition of magnesium sulphate to a bupivacaine-epinephrine mixture for interscalene nerve block prolonged the duration of analgesia and decreased postoperative pain after rotator cuff repair. From a clinical standpoint, the results might be modest because adding magnesium to bupivacaine did not reduce the postoperative opioid consumption.…”
Section: Discussionmentioning
confidence: 86%
“…Only patients with complete motor block were included in the study. Sedation was assessed using the sedation score described by Culebras et al 6 (1-awake and alert, 2-sedated, responding to verbal stimulus, 3-sedated, responding to mild physical stimulus, 4-sedated, responding to moderate or severe physical stimulus, 5-not arousable). Heart rate, noninvasive blood pressure, oxygen saturation and sedation score were measured every five minutes until the end of surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have investigated several adjuncts, including opioids, clonidine, neostigmine, hyaluronidase, and bicarbonate. [5][6][7][8][9] The results have been inconclusive, because of associated side effects or doubtful efficacy. Midazolam, a water-soluble benzodiazepine, is known to produce antinociception and to enhance the effect of local anesthetic when given epidurally or intrathecally.…”
Section: Conclusion : Le Midazolam (50 µG·kg -1 ) Combiné à 30 ML De mentioning
confidence: 99%